2020
DOI: 10.1038/s41467-020-18655-7
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal colloidal quantum dot inks enable efficient multilayer optoelectronic devices

Abstract: Surface ligands enable control over the dispersibility of colloidal quantum dots (CQDs) via steric and electrostatic stabilization. Today’s device-grade CQD inks have consistently relied on highly polar solvents: this enables facile single-step deposition of multi-hundred-nanometer-thick CQD films; but it prevents the realization of CQD film stacks made up of CQDs having different compositions, since polar solvents redisperse underlying films. Here we introduce aromatic ligands to achieve process-orthogonal CQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 40 publications
1
63
0
Order By: Relevance
“…We expect the solvent–ligand interaction to influence the fabrication of the HTL in state-of-art solar cells, where the exchange with 1,2-ethanedithiol (EDT) ligands, given the high reactivity of thiols, is fast and often leads to aggregation caused by the rapid volume contraction. However, the solvent’s role in the SLE exchange kinetics and CQD aggregation is not fully explored and its effects, in the context of the solar cell device, are not yet fully understood.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…We expect the solvent–ligand interaction to influence the fabrication of the HTL in state-of-art solar cells, where the exchange with 1,2-ethanedithiol (EDT) ligands, given the high reactivity of thiols, is fast and often leads to aggregation caused by the rapid volume contraction. However, the solvent’s role in the SLE exchange kinetics and CQD aggregation is not fully explored and its effects, in the context of the solar cell device, are not yet fully understood.…”
mentioning
confidence: 93%
“…From AFM measurements (Figure S3 in the Supporting Information), we calculated the RMS surface roughness and found a decreased surface roughness in the case of PRN (1.6 ± 0.2 nm) compared to ACN (2.8 ± 0.4 nm). Additionally, from SEM images, we observe in the PRN sample a reduced number of cracks, caused by volume shrinkage following rapid exchange (Figure S4 in the Supporting Information). We attribute this to the slower exchange kinetics, which minimize the rate of volume contraction.…”
mentioning
confidence: 99%
“…With n–i–p structure, the CQDSC with the MA‐PbS HTL can achieve a V oc of 0.64 V with a V oc loss of ≈0.45 V. Additionally, the group further introduced aromatic ligands to achieve the process‐orthogonal CQD inks, which can realize CQD film stacks. [ 202 ] The results revealed that the CQDs with aromatic ligands can achieve higher hole mobility and lower defect density, compared with those of EDT‐PbS HTLs. With n–i–p structure, the CQDSC with the CQD HTL of aromatic ligands can achieve a V oc of 0.52 V with a V oc loss of ≈0.39 V.…”
Section: Charge Transport Layermentioning
confidence: 99%
“…CQD inks—dispersions of CQDs capped with short conductive ligands—have recently been employed in high‐performing optoelectronic devices. [ 20,21 ] This is enabled by the combined effect of a high degree of surface passivation, [ 22 ] minimized energetic disorder, [ 20 ] and compatibility with scale‐up techniques, [ 23 ] as opposed to CQDs passivated by solid‐state ligand exchange. However, the reduced ligand length in CQD inks requires electrostatic colloidal stabilization, which complicates oriented assembly in CQD solids.…”
Section: Introductionmentioning
confidence: 99%